Behavioral Responses Of The German Cockroach, Blattella Germanica (L.) (Dictyoptera: Blattellidae) Towards Toxic Baits - Quah , Lay Tyng (2009)

(untitled)
This study focuses on the comparative performance of selected insecticide gel baits and the association between the feeding behaviour of German cockroaches, Blattella germanica (L.), and the toxicity of the baits. An arena test was conducted to evaluate the effectiveness of gel baits on three life stages of the German cockroach: adult males, adult females, and intermediate nymphs. A total of five commercial gel baits were tested and their effectiveness was evaluated by comparing their LT50 and LT95 values. The sequence of effectiveness of the baits from the least to greatest LT50 value (p = 0.05) was: fipronil = indoxacarb > imidacloprid > abamectin > hydramethylnon. However, the LT95 values were slightly different: fipronil = indoxacarb > abamectin > hydromethylnon > imidacloprid.